2003
DOI: 10.1161/01.str.0000080943.59701.0d
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Neuroprotective Agent Administration by Prehospital Personnel in an Urban Setting

Abstract: Background and Purpose-Studies have demonstrated the importance of early stroke treatment. If a neuroprotective agent (NA) clinical trial is successful, the greatest benefit might be attained with early prehospital administration. This study determined the potential reduction in time to treatment of stroke patients when NAs were administered in the prehospital setting. Methods-Twenty-three urban emergency medical services (EMS) agencies participated in this study. Prehospital personnel completed a stroke asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…30 Of importance for future research is the fact that it appears possible to incorporate EMS into the research process, with EMS personnel having demonstrated success in facilitating physician cell phone elicitation of consent from patients and in delivering experimental stroke therapy. 31,32 …”
Section: B Ems Managementmentioning
confidence: 99%
“…30 Of importance for future research is the fact that it appears possible to incorporate EMS into the research process, with EMS personnel having demonstrated success in facilitating physician cell phone elicitation of consent from patients and in delivering experimental stroke therapy. 31,32 …”
Section: B Ems Managementmentioning
confidence: 99%
“…Как показали многочисленные исследования, вызов бригады скорой медицинской помощи (СМП) ассоцииро-ван с более быстрой доставкой в стационар, нежели само-стоятельное обращение пациентов в больницу (поступле-ние «самотеком») [1][2][3][4][5][6][7][8][9].…”
Section: л е к ц и иunclassified
“…Thrombolysis is only safe and effective in selected cases of cerebral infarction, and would be disastrous in the context of cerebral haemorrhage. Inherent in this model is the inability to identify cerebral haemorrhage accurately on clinical grounds (Crocco et al 2003), as well as the variability of accurate stroke diagnosis by ambulance personnel. The sensitivity of stroke diagnosis varies widely (between 61% and 94%) and positive predictive values remain low (Rajajee & Saver 2005).…”
Section: The Development Of Variant Interhospital Collaborative Modelmentioning
confidence: 99%